Malignant pleural mesothelioma : a guide for clinicians - Giordano, Antonio, MD; Franco, Renato (Academic Press, an imprint of Elsevier, 2019)
Malignant Pleural Mesothelioma: A Guide for Clinicians is a practical book developed to assist clinicians, pathologist and molecular biologist in the management of malignant pleural mesothelioma (MPM). MPM represents a challenge in terms of diagnosis, staging and treatment, and to date, the optimal management of MPM patients has not yet been clearly defined - and this book is intended to be an efficient tool for these cases. The book encompasses topics such as epidemiology and surveillance evidence, multimodality imaging assessment of MPM, pathology, molecular mechanisms and treatment of such disease. Additionally, it discusses the standard operative procedures and the future directions for the management of MPM from experts' experiences. Malignant Pleural Mesothelioma: A Guide for Clinicians is a valuable source for oncologists, pathologist, cancer researchers, thoracic specialists and several members of biomedical field who needs to learn more from experts about the diagnosis, operative procedures and treatment of malignant pleural mesothelioma.